1994
DOI: 10.1002/jso.2930550110
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional support and prognosis in patients with head and neck cancer

Abstract: We retrospectively studied the relationship between nutritional status as indicated by the presence or absence of the cutaneous delayed hypersensitivity response and treatment-related morbidity, disease recurrence, and survival at 2 years in 67 consecutive patients with head and neck carcinoma. Serial nutritional assessments were conducted throughout the course of combined initial antineoplastic treatment and nutritional support. The presence of cell-mediated immunity at the end of treatment was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 25 publications
0
23
0
1
Order By: Relevance
“…Lopez et al retrospectively studied the correlation between immunocompetence and morbidity, tumor recurrence, and survival at 2 years for 67 head and neck cancer patients undergoing surgery in conjunction with postoperative radiotherapy. 38 Those authors found a 100% survival rate for patients with a normal immunologic response and a 48% survival rate for patients with an absent cutaneous delayed hypersensitivity response. Apart from the rather unusual observation of a 100% survival rate, the results of this study must also be interpreted with caution because impaired immunocompetence is not by definition synonymous with malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Lopez et al retrospectively studied the correlation between immunocompetence and morbidity, tumor recurrence, and survival at 2 years for 67 head and neck cancer patients undergoing surgery in conjunction with postoperative radiotherapy. 38 Those authors found a 100% survival rate for patients with a normal immunologic response and a 48% survival rate for patients with an absent cutaneous delayed hypersensitivity response. Apart from the rather unusual observation of a 100% survival rate, the results of this study must also be interpreted with caution because impaired immunocompetence is not by definition synonymous with malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…It may decrease the response to chemotherapy as well as the tolerance to both radio and chemotherapy (Dewys et al, 1980;Vigano et al, 1994). Artificial nutrition can limit the risk of malnutrition although it is unable to restore a severely altered nutritional state (Lipman, 1991;Lopez et al, 1994;Société Française de Nutrition Entérale et Parentérale et Société Française d'Anesthésie Réanimation, 1995;Shike, 1996;Souba, 1997;Barber et al, 1998). Enteral tube feeding (ETF) is the method of choice in patients with functional digestive tract (Campos et al, 1990;Boyd and Beeken, 1994;Bozetti, 1994;Société Française de Nutrition Entérale et Parentérale et Société Française d'Anesthésie Réanimation, 1995).…”
mentioning
confidence: 99%
“…ETF-related complications are uncommon, the most frequent being diarrhoea (Coben et al, 1994; Société Française de Nutrition Entérale et Parentérale et Société Française d'Anesthésie Réanimation, 1995). Acute aspiration pneumonia is rare and can easily be avoided (Lopez et al, 1994).…”
mentioning
confidence: 99%
“…This prospective study addresses the outcome of near-total laryngectomy in 54 consecutive advanced lesions of the larynx (14) or pyriform sinus (40) carried out by the senior author (A.M.S.) 12,13 Therefore, these procedures may be better avoided in clinical situations with a high potential for infection, such as radiotherapy failure and obstructive lesions in patients with prior tracheotomies. An earlier report from this center attested to the therapeutic efficacy of this surgical procedure, with satisfactory speech restoration with no tracheobronchial aspiration.f Before 1988, these patients would have undergone totallar-Shunt stenoses Shunt denervation Aspiration advantage (in >80%), without troublesome tracheobronchial aspiration (<10%), has indeed made this procedure worth the marginally increased hospital stay, Attention is being directed to minimizing the local wound problems that mar the convalescence, especially in patients with pyriform sinus lesions.…”
Section: Discussionmentioning
confidence: 99%